Islamic Banking Financial Performance in Indonesia and Malaysia: Analysis of Factors That Influence It - Hayuningtyas, Faizah Diah; Hartikasari, Annisa Ilma; Fakhruddin, Iwan; Pratama, Bima Cinintya (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2024)
This research focuses on the analysis of the financial performance of Islamic banks in Indonesia and Malaysia from 2018 to 2022. The study aims to determine the impact of Operational Expenses Compared to Operational Revenues (BOPO), Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Net Interest Margin (NIM), and Firm Size on the profitability (ROA) of Islamic banking in Indonesia and Malaysia. Using purposive sampling techniques, 24 banks were selected as samples, with 12 banks from Indonesia and 12 from Malaysia. Data analysis was conducted using multiple regression analysis. The results of the study indicate that (1) BOPO has a negative and significant contribution to the ROA of Islamic banks in Indonesia, while CAR and NPF show a positive correlation but not significantly; (2) NPF and NI affect the ROA of Islamic banks in Malaysia, while Firm Size shows a positive correlation but not significantly. These findings are expected to provide valuable insights for investors in making investment decisions, particularly in the banking sector in both Indonesia and Malaysia.